Sex Education Using Problem-Based Learning Approach: An Effort to Raise Adolescent Awareness of the Dangers of Promiscuity - Safitri, Yanuar; Nurhayati, Sri (Jurnal Simki Pedagogia, 2023)
The purpose of this study is to explain the implementation of sex education for teenagers using a problem-based learning method in Cibeureum Village, Cimahi City, to raise awareness of the dangers of promiscuity. This study used a qualitative method and employs a case study design. Observation, in-depth conversations, and documentation studies are all methods for gathering data. As study resource people, two community leaders, ten sex education participants, and three sex education program organizers were used.Techniques for data analysis include data condensation, data presentation, deriving conclusions, and verification. The research founds that: (1) Sex education for adolescents using a problem-based learning strategy is carried out in stages, beginning with program planning by the village government in collaboration with RT administrators, RWs, community leaders, and parents with teenagers. 2) sex education program organizers collaborate with competent resource people when conducting the program. In addition, material on the dangers of promiscuity for adolescents is presented using problem-based learning, in which resource people present material based on real issues encountered by adolescents as a result of promiscuity. 3) the majority of participants' insights and understanding of the dangers of promiscuity had grown, especially the material presented using a problem-based learning approach.